Peningkatan Kualitas Citra Radiograf Panoramik Menggunakan Metode Filter Laplacian - Haq, Haritsul; Oktamuliani, Sri; Putri, Wulandani Liza; Gunawan, Gunawan; Adnan, Surma (Jurnal Fisika Unand, 2024)
Image quality enhancement of panoramic radiographs using the Laplacian filter method has been carried out. This study aims to improve the quality of panoramic radiography images (Acteon X-Mind Prime 3D) in the radiology installation of RSGM Andalas University. This study used secondary data from 46 panoramic images in .BMP format, which were performed by applying Laplacian filter and evaluating image quality by Structural Similarity Index (SSI), Contrast-to-Noise Ratio (CNR), Contrast Improvement Ratio (CIR) and Spatial Frequency (SF). The results showed that the SSI value was 0.636 ± 0.0732, CNR 5.36 ± 0.412, CIR 0.740 ± 0.124, SF 0.605 ± 0.0983. These results mean that CNR shows good image contrast, SSI shows dissimilarity between the original image and the image after Laplacian filter processing, CIR shows good contrast improvement, while the SF value of 0.749 indicates that the image's ability to display structural details is still lacking. Skewness and Shapiro-Wilk tests indicate that SSI and SF are abnormally distributed, while CIR and CNR are normally distributed. T-test analysis was performed on the CIR and CNR metrics data, which showed that the significance of this study indicated that the Laplacian filter method was significant p < 0.001. Thus, the use of the Laplacian filter method significantly improves the image quality of panoramic radiographs.